Factors affecting customer loyalty on mobile internet subscription among non-resident students in UiTM Kedah / Siti Zahara Abdul Kareem and Noor llie Zuhaili Yahaya - Abdul Kareem, Siti Zahara; Yahaya, Noor llie Zuhaili (2018)
This chapter provides an overview of this study, which consists of eight main sections. Beginning with the background of study, this chapter identifies the issues ascertain the research problem, research problem and the objective of this research endeavour. It also highlights the significance, scope of the study, provides the definition of terms and concludes with a discussion on the remaining chapters.